ANALISIS POLA INTENSITAS RADIASI EM OLEH MATAHARI DALAM PEMBELAJARAN FISIKA LINGKUNGAN - Sudarti; Aulia Shinta Balqis; Nazwa Faizzatum Marisah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
The purpose of the analysis of the intensity of solar magnetic field radiation is to compare the results of temperature, humidity and magnetic field measurements with several location points such as indoors, outdoors, under trees, and under electric poles to be used as parameters in determining the value of the intensity of solar magnetic field radiation. The research method used is a direct observation method as the main process of data collection which is then collected through literature studies including books, scientific journals, conference articles, and trusted online sources and is included in the accurate category.